Sedimentary palaeoenvironment, petrography, provenance and diagenetic inference of the Anacleto Formation in the Neuquén Basin, Late Cretaceous, Argentina - Armas, María Paula (2014)
The Anacleto Formation is the uppermost unit of the Neuquén Group, which makes up the foreland stage infill of the Neuquén Basin, during Late Cretaceous. The detailed sedimentological study performed in the excellent outcrops of this formation on the eastern border of the basin allowed the identification of eight fluvial lithofacies, grouped into six facies associations. A meandering fluvial system with palaeo flows from the SW can be interpreted from distribution of facies associations, architectural framework, channel/floodplain ratio, etc. The compositional analysis of the sandstones was performed by mean of petrographic characterization and modal analysis. Sandstones of the Anacleto Fm are mainly subarkosic, arkosic, lithic arenites and, to a lesser extent, sublitoarenites (Q54-F25-R21; Q52-F24-L25). The composition suggests underlying igneous, metamorphic and sedimentary rocks in the main source area. Sedimentological and petrographic analyses, jointly with palaeocurrents orientations suggest that high areas of the North Patagonian Massif were the main source of the fluvial system. The diagenetic stages interpreted from the petrographic characters, SEM observations and X-ray diffraction determine eodiagenesis and telodiagenesis, which are consistent with the burial history of the Neuquén Group. Furthermore, palaeoclimatic considerations based on compositional analysis suggest semiarid to semihumid conditions for the deposition of the Anacleto Fm. These conditions are also supported by clay mineralogy that confirmed smectite as dominant species. A strong climatic seasonality is also deduced by the presence of calcrete levels and frequent discharge channels.